Confidence Interval of Single Dipole Locations Based on EEG Data - Braun, Christoph; Kaiser, Stefan; Kincses, Wilhelm-Emil; Elbert, Thomas (My University, 1997)
Noise in EEG and MEG measurements leads to inaccurate localizations of the sources. A confidence volume is used to describe the amount of localization error. Previous methods to estimate the confidence volume proved insufficient. Thus a new procedure was introduced and compared with previous ones. As one procedure, Monte Carlo simulations (MCS) were performed. The confidence volume was also estimated using two methods with different assumptions about a linear transfer function between source location and the distribution of the potential. One method used variable (LVM) and the other fixed dipole orientations (LFM). Finally, the confidence volume was estimated through a procedure in which there was no linearization of the transfer functions. This procedure scans the confidence volume by varying the dipole location in multiple directions. Confidence volumes were calculated for simulated distributions of the electrical potential and for experimental data including somatosensory evoked responses to stimulation of lower lip, thumb, and little finger. Results from simulated data indicated that confidence volumes calculated with the MCS method were largest, and those calculated with the LFM method were smallest. For dipole locations close to the brain surface, the confidence volume was smaller than for a central deeper source. An increase in electrode density resulted in smaller confidence volumes. When the noiose was correlated, only the method using the MCS produced acceptable results. Since the noise in experimental data is highly correlated, only the MCS method would appear to be useful in estimating the size of the confidence volume of the dipole locations. Thus, using real data with the MCS method, we easily distinguished separate and distinct representations of the thumb, little finger, and lower lip in the somatosensory cortex (SI). It was concluded that adequate estimation of confidence volumes is useful for localizing neural activity. On a practical level, this information can be used prior to an experiment for determining the conditions necessary to distinguish between different dipole sources, including the required signal to noise ratio and the minimum eletrode density.
Keywords: Confidence interval; 150; Dipolare Lokalisation; EEG; MEG; Monte Carlo